IMPLEMENTASI PELAYANAN ADMINISTRASI TERPADU - Mega Fitri (JIANA ( Jurnal Ilmu Administrasi Negara ), 2015)
Implementation of the Integrated Administrative Services. This study aims to identify and analyze the factors Implementation of the Integrated Administrative Service in the District Kuantan Singingi. Methods the research method used is descriptive research with a qualitative approach. Data was collected through interviews with informants consisting of Head, Head Secretary, Administration Section Chief, Section of Government staff and the people who never get a good service that the service licensing and non license in the District Kuantan District Office Singingi Singingi through observation and documentation. The data were analyzed with descriptive qualitative. The results showed that the factors that affect the implementation of the Integrated Administrative Service in District Kuantan Singingi seen from the communication factor, sources, trends and bureaucratic structures have not been so good. There are still many shortcomings encountered in its implementation in the field.